Analisis Pendapatan Dan Kelayakan Usaha Tani Cabai Merah Di Tani Arum Desa Sukorejo Kecamatan Parengan Kabupaten Tuban - Yudha, Danang Ananda; Yusdiantara, Yusdiantara; Wicaksono, Shendi (Manajemen Agribisnis: Jurnal Agribisnis, 2024)
Abstract Red chilies are a superior commodity that is always needed by the community. Apart from being a kitchen spice, it is also used as a natural coloring and as a cooking decoration. However, the need for red chilies is not only limited to household-scale consumers but also extends to factory- or industrial-scale. This research was conducted at Tani Arum, Sukorejo village, Parengan subdistrict, and Tuban district. The sample of respondents in this study were 15 farmers who farmed red chilies, out of a total of 58 farmers using a purposive sampling method. Determining the number of respondents used the Slovin formula. This research was carried out from July 2023 to September 2023. The aim of this research was to determine the income and feasibility of red chili farming in Tani Arum, Sukorejo Village, Parengan District, Tuban Regency. The method in this research uses quantitative and descriptive analysis. Based on the research results, it was found that the income obtained by farmers in Tani Arum, Sukorejo Village, Parengan District, and Tuban Regency was an average of IDR 45,539,654/ha per farmer. The feasibility of red chili farming in Poktan Tani Arum in Sukorejo village, Parengan sub-district, Tuban district has an average revenue value of IDR. 22,085,714.-/ha/farmer and an R/C ratio of 3.5, which means red chili farming is worth pursuing. Keywords: red chilies, farmer, income, feasibility